Idiomatic Expressions Found in Taylor Swift’s Song “Shake It Off” Lyrics - Tsulis Khoerunnisa Amanah; Otong Setiawan Djauhari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
The present study aims to identify and analyse idiomatic expressions in the lyrics of "Shake It Off" by Taylor Swift. Idioms are a form of non literal expression which often pose a challenge for English language learners, due to the fact that their literal meanings are not easily discernible. Utilising a descriptive qualitative approach, this research analyses idioms based on Makkai's (1972) classification, which includes six types: phrasal verb idioms, tournure idioms, irreversible binomial idioms, phrasal compound idioms, incorporating verb idioms, and pseudo idioms. The findings indicate that the composition is replete with idiomatic usage, reflecting emotional meanings and social messages implicitly. A total of fourteen idioms were identified, which serve to reinforce Taylor Swift's stylistic language and make the song an effective and contextual medium for the purposes of English language learning. It is anticipated that these findings will contribute to the development of language teaching, particularly with regard to the comprehension of idiomatic meaning within the context of popular culture.